2005
DOI: 10.1111/j.1600-0854.2005.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles for Cyclin G‐Associated Kinase in Clathrin‐Mediated Sorting Events

Abstract: Cyclin G-associated kinase (GAK), also known as auxilin 2, is a potential regulator of clathrin-mediated membrane trafficking. It possesses a kinase domain at its N-terminus that can phosphorylate the clathrin adaptors AP-1 and AP-2 in vitro. The GAK C-terminus can act as a cochaperaone in vitro for Hsc70, a heat-shock protein required for clathrin uncoating. Here we show that the specificity of GAK is very similar to that of adaptor-associated kinase 1, another mammalian adaptor kinase. We used siRNA to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(133 citation statements)
references
References 49 publications
8
125
0
Order By: Relevance
“…In agreement with previous reports (Greener et al, 2000;Zhang et al, 2005;Lee et al, 2006), immunofluorescence microscopy analyses showed that a fraction of endogenous GAK colocalized with TGN46 ( Figure 6, A-C), clathrin ( Figure 6, D-F), and AP1 (Figure 6, G-I) at the TGN. Treatment with brefeldin A (BFA), which dissociates Arf1-regulated coat proteins such as AP1 from membranes (Robinson and Kreis, 1992;Wong and Brodsky, 1992), redistributed GAK to the cytosol ( Figure 6, J-L).…”
Section: Association Of Gak With the Tgn Is Dependent On Ap1supporting
confidence: 78%
See 3 more Smart Citations
“…In agreement with previous reports (Greener et al, 2000;Zhang et al, 2005;Lee et al, 2006), immunofluorescence microscopy analyses showed that a fraction of endogenous GAK colocalized with TGN46 ( Figure 6, A-C), clathrin ( Figure 6, D-F), and AP1 (Figure 6, G-I) at the TGN. Treatment with brefeldin A (BFA), which dissociates Arf1-regulated coat proteins such as AP1 from membranes (Robinson and Kreis, 1992;Wong and Brodsky, 1992), redistributed GAK to the cytosol ( Figure 6, J-L).…”
Section: Association Of Gak With the Tgn Is Dependent On Ap1supporting
confidence: 78%
“…Although it is now clear that both the expression of GAK (Lee et al, 2005;Zhang et al, 2005; this study) and its ability to interact with AP1 (this study) are required for lysosomal enzyme sorting, the exact mechanism by which GAK participates in this process remains to be elucidated. GAK contains a Ser/Thr kinase domain homologous to that of AAK1, an enzyme that phosphorylates the 2 subunit of AP2 and activates it for recognition of YXXØ-type sorting signals Ricotta et al, 2002;Honing et al, 2005).…”
Section: How Does Gak Participate In Lysosomal Enzyme Sorting?mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, AAK1 shares with Prk1p not only the extensive kinase sequence homology but also the similar recognition motif Ricotta et al, 2002). Another mammalian homologue of Prk1p, GAK, also exhibits a similar specificity on the 2 subunit and plays a regulatory role in endocytosis (Zhang et al, 2005). AP2 is known to associate with Eps15, the mammalian counterpart of Pan1p, and such interaction is required for endocytosis (Benmerah et al, 1995(Benmerah et al, , 1998.…”
Section: Other Considerationsmentioning
confidence: 99%